2020
DOI: 10.1016/j.jconrel.2019.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles with antioxidant enzymes protect injured spinal cord from neuronal cell apoptosis by attenuating mitochondrial dysfunction

Abstract: In spinal cord injury (SCI), the initial damage leads to a rapidly escalating cascade of degenerative events, known as secondary injury. Loss of mitochondrial homeostasis after SCI, mediated primarily by oxidative stress, is considered to play a crucial role in the proliferation of secondary injury cascade. We hypothesized that effective exogenous delivery of antioxidant enzymessuperoxide dismutase (SOD) and catalase (CAT), encapsulated in biodegradable nanoparticles (nano-SOD/CAT) -at the lesion site would pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 39 publications
1
61
0
Order By: Relevance
“…Similar to previous studies, we observed that Brd4 expression is elevated in neurons using a ROS donor, and JQ1 treatment promotes the increased expression of HO-1 and SOD1, both of which have been identified as effective antioxidant enzymes. In addition, oxidative stress is important in promoting apoptosis, and the occurrence of neural apoptosis results in irreversible neural tissue loss both in primary and adjacent injury sites after SCI ( Andrabi et al, 2020 ). In the present study, the results suggested that the inhibition of Brd4 by JQ1 maintains the neural homeostasis and survival of injured spinal cord tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous studies, we observed that Brd4 expression is elevated in neurons using a ROS donor, and JQ1 treatment promotes the increased expression of HO-1 and SOD1, both of which have been identified as effective antioxidant enzymes. In addition, oxidative stress is important in promoting apoptosis, and the occurrence of neural apoptosis results in irreversible neural tissue loss both in primary and adjacent injury sites after SCI ( Andrabi et al, 2020 ). In the present study, the results suggested that the inhibition of Brd4 by JQ1 maintains the neural homeostasis and survival of injured spinal cord tissue.…”
Section: Discussionmentioning
confidence: 99%
“…PVAX has shown effectiveness in different types of I/R injuries, including hind limb I/R, liver I/R as well as cardiac I/R [97,98]. Andrabi et al used biodegradable nanoparticles (nano-SOD/CAT) to encapsulate the antioxidant enzymes superoxide dismutase (SOD) and catalase (CAT) to effectively deliver those enzymes at the lesion site to protect mitochondria from oxidative stress, therefore protecting the spinal cord from secondary injury [99]. Tapeinos et al have developed biodegradable PLGA microspheres coated with collagen type I and MnO 2 nanoparticles to scavenge ROS and protect cells from apoptosis induced by oxidative stress [100].…”
Section: Antioxidant Deliverymentioning
confidence: 99%
“…[18][19][20][21][22] Moreover, the easy distribution of ROS into the neighboring area of the injured site often causes the expansion of the injured site, leading to aggravated secondary injury with more serious locomotion defects. 16,23 Therefore, the scavenging of ROS has been established to be an effective route to attenuate secondary injury in acute TSCI treatment. 20,21,[23][24][25] In the present study, a type of selenium-doped carbon quantum dots (Se-CQDs) was prepared and used for effectively ameliorating secondary TSCI ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…16,23 Therefore, the scavenging of ROS has been established to be an effective route to attenuate secondary injury in acute TSCI treatment. 20,21,[23][24][25] In the present study, a type of selenium-doped carbon quantum dots (Se-CQDs) was prepared and used for effectively ameliorating secondary TSCI ( Figure 1). The Se-CQDs were prepared via a simple approach, ie, hydrothermal treatment of L-selenocystine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation